Language contact and Linguistic Borrowings - Bojaxhi, Jola (European Journal of Social Science Education and Research, 2023)
Nowadays multilingualism, where a speaker has more than two languages, is not uncommon. But bilingualism and multilingualism differ from language shift or a permanent change in a person’s choice of language for everyday purposes. The purpose of this paper is to highlight the cases of borrowing usage and the features they represent while integrating into the Albanian language. Unnecessary borrowings are many, and a way should be considered for their replacement so that expressive and regenerative language skills create the ability to preserve its features and identity by developing them further.
Keywords: language, communication, borrowings, linguistic, mother tongue.